A Comprehensive Review for Phytochemical, Pharmacological, and Biosynthesis Studies on Glycyrrhiza spp - Wang, Chengcheng; Chen, Lihong; Xu, Chaoqie; Shi, Jingjing; Chen, Shuyu; Tan, Mengxia; Chen, Jiali; Zou, Lisi; Chen, Cuihua; Liu, Zixiu; Liu, Xunhong (The American journal of Chinese medicine (1979), 2020)
Licorice is extensively applied in food as well as herbal medicine across the world, possessing a substantial share in the global market. It has made great progress in chemical and pharmacological research in recent years. Currently, Fisch., Bat., and L. were officially used as Gan-Cao according to the Chinese Pharmacopoeia. Accumulating evidence demonstrated three varieties of licorice have their own special compounds except for two quality markers set by Pharmacopoeia, providing great possibility for better understanding their characteristics, evaluating quality of each species and studying biosynthesis mechanisms of species-specific compounds. As a special "guide drug" in clinic, licorice plays an important role in Chinese herbal formulas. The interaction between licorice with other ingredients and their metabolism should also be taken into consideration. In addition, draft genome annotation, and success of the final step of glycyrrhizin biosynthesis have paved the way for biosynthesis of other active constituents in licorice, a promising beginning of solving source shortage. Accordingly, we comprehensively explored the nearly 400 chemical compounds found in the three varieties of licorice so far, systematically excavated various pharmacological activities, including metabolism via CYP450 system , and introduced the complete biosynthesis pathway of glycyrrhizin in licorice. The review will facilitate the further research toward this herbal medicine.